Does Profitability Mediate the Influence of Corporate Governance on Firm Value? - Niken Wulandari; M. Farid Wajdi; Ihwan Susila; Imronudin Imronudin (Petra International Journal of Business Studies, 2022)
This study examines the effect of corporate governance on firm value with profitability as an intervening variable. This study uses a sample of banking companies listed on the Indonesia Stock Exchange in 2016-2020. The sampling technique used was the purposive sampling technique. This type of research is quantitative with path analysis using the software Eviews 9. The results of this study indicate that: 1) Independent commissioners and institutional ownership have no significant effect on the profitability variable, while the board of directors, public ownership, and managerial ownership have a significant positive effect on profitability. 2) Profitability has a significant positive effect on firm value. 3) Public ownership and managerial ownership have a significant positive effect on firm value, while independent commissioners, board of directors, and institutional ownership have no significant effect on firm value. 4) Independent commissioners and institutional ownership have no significant effect on firm value through profitability. Meanwhile, the board of directors, public ownership, and managerial ownership positively and significantly affect firm value through profitability.